A hermeneutic research on project management approaches applied in a business process re-engineering project. Issue 8 (8th September 2022) - Musonda, Innocent; Okoro, Chioma Sylvia
Abstract : Purpose: Business process re-engineering (BPR) initiatives are complex endeavours which require many factors to ensure success. However, most studies focus on the organisational processes and improvement within the organisation itself and less on the project team and management dynamics. The study aimed to identify factors that enabled the completion of a BPR, in a technical firm, based on reflections on the project management style. Design/methodology/approach: The study entailed a descriptive and interpretive case study with reflections from project team members. Data were analysed using descriptive statistics and content analysis. Findings: Findings revealed that critical success factors for BPR in a technical firm include project leadership and sponsorship, organisational culture and attributes, team dynamics and the nature (activities), and duration of the process. Practical implications: The findings will benefit project managers in improving their competence and project success through reflective practice. The identified factors could be used in future projects of a similar nature and size to improve how organisations execute BPR projects. Originality/value: The study used reflections to identify success factors for BPR in a technical firm.